Self Determination and Quality of Life: a Comparison of the Measurement Scales for Students with Intellectual Disabilities - Zappella, Emanuela (Journal of Child and Adolescent Psychiatry, 2019)
Self-determination is a key concept to promote greater self-awareness in the subjects with disability, to build appropriate educational or professional projects and to evaluate the already active programs. Using PRISMA checklist, I selected articles from different databases (CINAHL, Medline, Psych INFO, Cochrane Library, ERIC, Scholar. The 9 evaluation measures identified are analyzed with respect to: choice of the points of view to be collected, domains, items and data collection methods. The results show that while some scales focus on autonomy, empowerment, self-realisation and self-regulation and others focus on knowledge, skills and abilities, attitudes and beliefs. Two instruments added also: opportunities and support. With respect to the choice of the points of view to be collected: in some cases the student’s opinion is collected but in other cases their point of view is integrated or replaced with that of teachers and parents. Only one tool is designed for all children and starts from the belief that self-determination is important for all people, including those with a disability. A third element of the analysis is the possibility of answering the questions posed by the various evaluation tools. A typical form is Likert scale while in other cases open questions are used. The analysis highlights two critical issues. The variety of definitions of self-determination is inevitably reflected in the choice of domains and items and therefore self-determination is only partially investigated. Secondly the opinion and people with disabilities are sometimes completed or replaced by that of third persons as parents and teachers. Starting from the analysis of existing instruments. the article closes with a reflection on the possibility of constructing a scale that considers all the aspects of self-determination offered in the literature (at the individual and environmental level) and collects the opinion of all the subjects involved in self-determination projects. This synthesis represents a first step in the construction of a possible universal scale starting from the analysis of the literature. A comparison would then be necessary with the students with intellectual disabilities, the family members and the other actors involved to understand which domains are really meaningful to them and to build indicators that correspond to the elements that are important to them. In this way we would have a tool capable of combining the point of view of literature with that of the people directly involved.
Keywords: self determination; student with intellectual disability; quality of life; evaluation scale